Asymmetric activation of the calcium-sensing receptor homodimer - Gao, Y; Robertson, MJ; Rahman, SN; Seven, AB; Zhang, C; Meyerowitz, JG; Panova, O; Hannan, FM; Thakker, RV; Bräuner-Osborne, H; Mathiesen, JM; Skiniotis, G (Springer Nature, 2021)
The calcium-sensing receptor (CaSR), a cell-surface sensor for Ca2+, is the master regulator of calcium homeostasis in humans and is the target of calcimimetic drugs for the treatment of parathyroid disorders1. CaSR is a family C G-protein-coupled receptor2 that functions as an obligate homodimer, with each protomer composed of a Ca2+-binding extracellular domain and a seven-transmembrane-helix domain (7TM) that activates heterotrimeric G proteins. Here we present cryo-electron microscopy structures of near-full-length human CaSR in inactive or active states bound to Ca2+ and various calcilytic or calcimimetic drug molecules. We show that, upon activation, the CaSR homodimer adopts an asymmetric 7TM configuration that primes one protomer for G-protein coupling. This asymmetry is stabilized by 7TM-targeting calcimimetic drugs adopting distinctly different poses in the two protomers, whereas the binding of a calcilytic drug locks CaSR 7TMs in an inactive symmetric configuration. These results provide a detailed structural framework for CaSR activation and the rational design of therapeutics targeting this receptor.